A new species of Bottosaurus (Alligatoroidea: Caimaninae) from the Black Peaks Formation (Palaeocene) of Texas indicates an early radiation of North American caimanines. Issue 1 (4th April 2020) - Cossette, Adam P
Abstract: Morphological and molecular data suggest a close relationship for alligators and caimans. The first fossil appearances combined with phylogenetic hypotheses suggest a divergence of the groups near the Cretaceous–Palaeogene boundary, but the early fossil record of Caimaninae is incomplete, and large gaps exist between the earliest representatives of the group. A new caimanine from lower Palaeocene (Tiffanian) deposits in the Black Peaks Formation of Brewster County, Texas is established upon two specimens of different size that bear similarities to Bottosaurus harlani from the uppermost Cretaceous and lowermost Palaeogene of New Jersey. The larger individual consists of a partial skull and lower jaw in addition to postcranial material. The smaller individual preserves a snout and posterior portions of the skull. Both specimens suggest an animal with a comparatively short, flat, broad snout. Species of Bottosaurus share diagnostic morphological character states but are differentiated in meaningful ways. Phylogenetic analysis shows that the new species is sister to B. harlani, indicates an early radiation of North American caimanines and elucidates a more complicated biogeographical history than previously hypothesized. A growing body of evidence suggests that Caimaninae may be diagnosed by ancestral characters, potentially drawing basal alligatoroids crownwards in phylogenetic trees.